The Incursion of the Sublime in Ethics according the Kantian Precritical Period - Oroño, Matías (2015)
The main objective of this paper is to investigate the originality of the kantian treatment of the sublime. We will study the version corresponding to the pre-critical period, in order to point out that even in this period Kant distances himself from the dominant mode of analysis, represented by Edmund Burke’s work. We think that the novelty of the kantian approach lies in the close link established between the sublime and ethics.